CHILD LABOUR IN SPORTING ACTIVITIES (Fiep Bulletin - online, 2013)
This article aims at demonstrating that the sport with young athletes (children and adolescents) may consist in a form of dissimulated child labour, and, as such, is forbidden by the national legal system. In this regard, it undertakes an analysis of the child labour in general, concluding that the sporting practice by young athletes can be fit as one of its forms, since there can be pointed the five essential elements of the employment relationship: natural person, non-eventuality, personality, being onerous, subordination. It concludes by the application of the specific nullities theory of Labour Law, preserving the already produced effects, and by the necessity of recognizing and monitoring this job modality, in order to protect the physical, mental and moral development of these young athletes
Keywords: child labour; sports; nullities